Um novo método para quantificar mercúrio orgânico (Hg orgânico) empregando a espectrometria de fluorescência atômica do vapor frio - Bisinoti, Márcia Cristina [UNESP]; Jardim, Wilson F.; Brito Júnior, José Lailson; Malm, Olaf; Guimarães, Jean Remy (Sociedade Brasileira de Química, 2006)
In this work a simple and sensitive procedure to extract organic mercury from water and sediment samples, using methylene chloride in acidic media followed by CVAFS quantification has been developed. The method was evaluated for possible interferents, using different inorganic mercury species and humic acid, no effects being observed. The detection limit for organic mercury was 160 pg and 396 pg for water and sediment samples respectively. The accuracy of the method was evaluated using a certified reference material of methylmercury (BCR-580, estuarine sediment). Recovery tests using methylmercury as surrogate spiked with 1.0 up to 30.0 ng L-1 ranged from 90 up to 109% for water samples, whereas for sediments, recoveries ranged from 57 up to 97%.
A novel approach to quantify organic mercury (organic Hg) by cold vapour atomic fluorescence spectroscopy (CVAFS)
Keywords: methylmercury; bromine chloride; environmental samples